INFLUENCE OF BRAND AND PRODUCT QUALITY ON CUSTOMER’S BUYING DECISION IN SOUTH CIKARANG BEKASI REGENCY - Niantoro Sutrisno; Anisya Dwi Haryani (JURNAL LENTERA BISNIS, 2017)
The purpose of this study is to identify, analyse and assess the influences of Brand and Product Quality On Customer’s Buying Decision in South Cikarang Bekasi Regency. This research is intended to give advice for Brand and Product Quality On Customer’s Buying Decision in South Cikarang Bekasi Regency. This research was used descriptive and verification method. Descriptive research is used to describe characteristics of a population or phenomenon being studied. Verification is the research conducted with the aim to prove the truth of a theory on a particular time and place. The results of this research shown that there is a relationship between Brand and Product Quality. Meanwhile, Brand and Product Quality has the influence partially to the Customer’s Buying Decision. Besides that, Brand and Product Quality has the influence simultaneously to the Customer’s Buying Decision. Keywords: Brand, Product Quality, Bustomer’s Buying Decision